MORPHOLOME ANALYSIS FOR PREDICTION OF GENE FUNCTIONS - Dr Jerome Brathwaite, Dr. Jhon Klir, Dr Gauhar Hassan, Dr Bheemesh Vangalapati, Dr Sharique Ahmad, Ms Subuhi Anwar (South Eastern European Journal of Public Health, 2025)
One of the most important aspects of contemporary biology understands gene activities, which has ramifications for everything from basic science to real-world applications in biotechnology and medicine. One relatively new technology that has shown promise for predicting gene functions is morpholome analysis. Morpholome analysis is a thorough method of determining the functions of genes that involves systematically characterizing morphological phenotypes caused by genetic alterations. Morpholome analysis provides insights into the functional effects of gene alteration by combining high-throughput imaging, computational analysis, and functional genomics. This tool annotates gene functions and identifies new regulatory networks. This review emphasizes the role morpholome analysis plays in driving personalized medicine approaches, enabling drug discovery and development, and improving understanding of biological systems. The discovery of genes and pathways driving several of biological processes, including development, disease progression, and cellular signalling, is among the most significant results. Furthermore, advances in morpholome analysis approaches and technology have the potential to stimulate innovation and discovery across a wide range of biological and biomedical disciplines. To summarize, morpholome analysis is an important method for understanding gene activities, interpreting molecular pathways, and converting results into therapeutic applications for human disease and health.